2000
DOI: 10.1606/1044-3894.1089
|View full text |Cite
|
Sign up to set email alerts
|

“Mi Casa Es Su Casa”: Beginning Exploration of Mexican Americans' Natural Helping

Abstract: This article presents the findings of a pilot study on natural helping among Mexican Americans conducted in a large urban area of the Southwest. Twelve community-identified natural helpers were interviewed using the “Natural Helper Interview Schedule” utilized in previous studies in other parts of the country with European American subjects. As expansion of the earlier studies, the interview schedule was translated into Spanish and assessed for cultural appropriateness. The similarities found between the findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…It involves training informal advice-givers (Promotoras) that are already a part of the community to reach out to and help the underserved. Such advocacy roles appear to be an integral part of the Mexican and Mexican American experience (Patterson & Marsiglia, 2000), and the Promotora model builds on this aspect.…”
Section: The Promotora Modelmentioning
confidence: 99%
“…It involves training informal advice-givers (Promotoras) that are already a part of the community to reach out to and help the underserved. Such advocacy roles appear to be an integral part of the Mexican and Mexican American experience (Patterson & Marsiglia, 2000), and the Promotora model builds on this aspect.…”
Section: The Promotora Modelmentioning
confidence: 99%
“…In a study of Puerto Rican families, 24 identified the neighborhood school as an important resource in the community with personnel and teachers as part of the natural support system because they did so much that went beyond their job description (Delgado, 1998). Among Mexican Americans' natural supports were relatives, neighbors and friends (Patterson & Marsiglia, 2000) similar to the Dine (Navajo American) community where helpers included teachers or mentors who strengthened their ability to cope with life stressors (Waller & Patterson, 2002).…”
Section: Community Resilience Is Defined Asmentioning
confidence: 99%
“…Natural support systems are valuable because of the significance they hold for the individuals who depend on them and for the power they represent within communities. New immigrants depend on these sources of natural support systems for their self-protection and support (Portes & Stepick, 1985) and to buffer stress (Patterson & Marsiglia, 2000). These systems of support facilitate the coming together of individuals for resources such as for health benefits (Putnam, 2007).…”
Section: Community Resilience Is Defined Asmentioning
confidence: 99%
“…Immigration can dislocate families and seriously limit their ability to rely on relatives, compadres (ritualistic relatives), and friends (Patterson & Marsiglia, 2000). The longer they live in the United States, the more likely that Mexican American parents will become less strict and take on more American-like behaviors, hence increasing their preadolescents' exposure to risk (Rodríguez & Olswang, 2003).…”
Section: Ethnicity and Preadolescent Substance Usementioning
confidence: 99%